Study the release kinetics of curcumin released from PVA/curcumin composites and its evaluation towards hepatocarcinoma - Doaa Essamey El-Nashar, Nehad Naem Rozik, Abdel Mohsen Soliman, Fahima Helaly (Journal of Applied Pharmaceutical Science, 2016)
The polymer composites based on Polyvinyl alcohol loaded with different concentrations of commercial curcumin were prepared to be applied forcontrolled release drug delivery system to overcome the growth promotion of tumor cells. The prepared composites were subjected to drug release in aqueous media at room temperature. It was found that the amount of the released curcumin changed according to different pH media and the concentration of the loaded drug onto the polymer carrier. The diffusion coefficient of the released curcumin from the prepared composites was found to be 2.739X10-2, 1.638X10-2, and 5.777X10-4 in basic, acidic and neutral solution respectively according to Higuch's equation. The results of the in/vitro cytotoxic activity of the released curcumin showed sustained antiproliferative potency up to 30 % growth inhibition against the human liver cancer cell line (HEPG2) which extended to 25 days, to overcome hepatocarcinoma.
Keywords: Curcumin, Polyvinyl alcohol (PVA), slow release, anticancer drug.